2022
DOI: 10.2147/ijgm.s358139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Altitude on Hemoglobin and Red Blood Cell Indices in Adults in Different Regions of Saudi Arabia

Abstract: Purpose Complete blood count (CBC) is a commonly used blood test for health checks. This study was conducted to compare CBC from two different altitudes and from sea-level populations in order to suggest correction factor for altitude-related increment on the hemoglobin and red blood cell indices. Patients and Methods In this retrospective lab records study, large datasets of CBCs over 5-year period were screened from three different regions of Saudi Arabia, Jeddah (a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For females, the results were equally revealing. [11,12]. These results elucidate the specific variations in females, adding a new dimension to our understanding of high-altitude acclimatization.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…For females, the results were equally revealing. [11,12]. These results elucidate the specific variations in females, adding a new dimension to our understanding of high-altitude acclimatization.…”
Section: Discussionmentioning
confidence: 55%
“…For males, the study found significant variations in all CBC parameters except NEU (P=0.8696), as shown in Table 3 . Specifically, the mean HGB for males was 169.8±10.63 in Taif and 144.6±13.96 in Jeddah (P<0.0001) while the mean PLT was 289.7±65.00 in Taif and 249.0±60.07 in Jeddah (P<0.0001) [ 8 - 11 ]. These findings highlight the distinct hematological adaptations in males in response to high altitude due to hypoxia [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations